The Influence of Organizational Environment, Work Motivation and Organizational Commitment on Intention to Quit Through Job Satisfaction of Four-Star Hotel Employees in Surabaya - Hendro Rumpoko; Budiyanto; Nur Fadjrih Asyik (East Asian Journal of Multidisciplinary Research, 2022)
This study analyzed the intention to quit to a decision upon the perception of the problem of work expected of employees is not able to provide satisfaction the work done. Is associated with increased intention to quit of employees. The purpose of this study examines the factors that affect intention to quit, including the organizational environment, work motivation and organizational commitment. This study uses a quantitative description of the method by the method of eksplanatory, and samples taken of many as 200 respondents of the Four-Star Hotel in Surabaya. The testing data analysis was performed using SEM and test the research instruments. The results showed that the environment of the organization and the gratification of the work has a positive and significant influence on the intention to quit which is indicated by the magnitude of the influence of each 0,263 at a significance level of 0.027 < 0.05 and 0,247 at a significance level of 0,023 < 0,05.